Analisis Perbandingan Kinerja Traktor Tangan dan Smart Traktor Sensor GPS Berdasarkan Studi Literatur Prisma di Pertanian Lahan Basah - Saputri, Dellah Tian; Rejo, Amin; Adhiguna, Rizky Tirta (Jurnal Locus Penelitian dan Pengabdian, 2026)
Technological advancements in agriculture have driven the development of Global Positioning System (GPS)-sensor-based smart tractors to overcome the limitations of conventional hand tractors, especially in wetland areas with challenging field conditions. This study aims to analyze the performance comparison between hand tractors and GPS-sensor smart tractors using the Systematic Literature Review (SLR) approach based on the PRISMA method. From 60 reviewed articles, 15 met the inclusion criteria and were thoroughly analyzed. The results indicate that smart tractors excel in navigation accuracy, work path efficiency, and real-time data documentation, although they require higher initial investment. Conversely, hand tractors remain relevant for small-scale farmers due to their lower operational and maintenance costs. This evaluation provides a comprehensive overview of the effectiveness of both technologies and their implications for wetland agricultural productivity. The study recommends further development of smart tractors that are more adaptive, cost-effective, and suitable for the local farming context in Indonesia.